Hardening liquid composition and hardened transparent optical nylon
By using the multifunctional epoxy polyurethane, silane hydrolysate and epoxy curing agent in the hardening liquid composition, a high hardness and high light transmission hardening coating is formed, which solves the problem of insufficient hardness of optically transparent nylon and the impact of performance of conventional hardening coatings, and achieves the effect of improving the hardness and wear resistance of nylon lenses.
Patent Information
- Application Number
- CN202411866454.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
Optical transparent nylon has low hardness and is prone to wear on the surface, affecting its high light transmittance and imaging quality. Conventional silicone hardening coatings are not suitable for optically transparent nylon, which can lead to a decrease in Abbe number and refractive index.
A hardening liquid composition is developed, which contains 20-50 parts of multifunctional epoxy polyurethane, 40-80 parts of silane hydrolysate and 0.3-2 parts of epoxy curing agent, and a high hardness, high light-transmitting hardening coating is formed by heating curing. The multifunctional epoxy polyurethane used in this composition has a high refractive index and a plurality of epoxy groups, which can react with a silane hydrolysate and an epoxy curing agent to form a high hardness coating.
While maintaining the high light transmittance and Abbe number of optically transparent nylon, it significantly improves its hardness and wear resistance, avoiding the negative impact of conventional hardening coatings on the performance of nylon lenses.
Smart Images

Figure BDA0005194473490000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hardened coatings and relates to a hardening liquid composition and hardened transparent optical nylon. Background Art
[0002] Optically transparent nylon has a light transmittance of 90-92%, which is similar to that of optical glass. It has high refractive index (above 1.50), high barrier properties, excellent boiling resistance and other properties. It can be used as packaging materials for food, precision instruments, meters, pharmaceutical chemicals, etc. The industry is currently studying to further expand its applications, such as using it as a lens. The Abbe number of nylon lenses can reach 52, while the Abbe number of PC lenses is only about 30. Therefore, nylon lenses have better imaging quality and clearer visual effects. However, the hardness of optically transparent nylon is not high, and the surface is easily worn, which affects the appearance or performance, such as high light transmittance. Therefore, it is necessary to study the surface hardening layer of optically transparent nylon to increase its hardness and enhance its wear resistance.
[0003] For optically transparent materials, such as commonly used PC resin, a layer of high-transmittance silicone hard coating is generally applied on the surface to improve scratch and abrasion resistance. However, the applicant found that conventional silicone hard coating is not suitable for optically transparent nylon, which will lead to a decrease in the Abbe number and refractive index of nylon lenses.
[0004] Therefore, it is necessary to develop suitable optically transparent nylon hardening coating materials. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a curing liquid composition and a curing transparent optical nylon.
[0006] The technical solution of the present invention is as follows:
[0007] A curing liquid composition, wherein the raw material components include, by weight: 20-50 parts of multifunctional epoxy polyurethane, 40-80 parts of silane hydrolyzate and 0.3-2 parts of epoxy curing agent;
[0008] The number of epoxy groups in the multifunctional epoxy polyurethane is not less than 3, and the refractive index of the multifunctional epoxy polyurethane is not less than 1.53.
[0009] Preferably, the raw materials for preparing the multifunctional epoxy polyurethane are a combination of a polyol compound, xylylene diisocyanate and a hydroxy epoxy compound.
[0010] More preferably, the hydroxy epoxy compound is selected from one or a combination of two or more of glycidyl alcohol, ethylene glycol monoglycidyl ether, diethylene glycol monoglycidyl ether, propylene glycol monoglycidyl ether and dipropylene glycol monoglycidyl ether.
[0011] Preferably, the raw materials for preparing the silane hydrolyzate at least include a phenyl silane coupling agent and an amino-containing silane coupling agent.
[0012] More preferably, the structure of the phenylsilane coupling agent is as shown in the following formula (1):
[0013] R 1 (CH 2 ) a Me b Si(OR 2 ) 3-b (1)
[0014] Among them, R 1 is selected from phenyl or alkyl-substituted phenyl, R 2 Selected from C1-C4 alkyl, Me represents methyl, a=2-4, b=0-1.
[0015] More preferably, the weight proportion of the phenylsilane coupling agent in the raw materials for preparing the silane hydrolyzate is not less than 20%.
[0016] More preferably, the structure of the carbon-carbon double bond-containing silane coupling agent is as shown in the following formula (2):
[0017] R 3 NHR 4 Me c Si(OR 5 ) 3-c (2)
[0018] Among them, R 3 is selected from H or C1-C4 alkyl, R 4 is absent, C1-C4 alkylene or substituted C3-C8 alkylene, R 5 Selected from C1-C4 alkyl, Me represents methyl, c=0-1.
[0019] More preferably, the weight proportion of the aminosilane coupling agent in the raw materials for preparing the silane hydrolyzate is 3-10%.
[0020] A hardened transparent optical nylon comprises a transparent optical nylon and a hardened layer arranged on the surface of the transparent optical nylon, wherein the hardened layer is prepared from the hardening liquid composition described in any one of the above technical solutions.
[0021] Preferably, the hardening liquid composition is cured by heating to form the hardened layer.
[0022] The beneficial effects of the present invention are:
[0023] (1) In the present invention, multifunctional epoxy polyurethane is added to the silane hydrolyzate. The multifunctional epoxy polyurethane can react with the silane hydrolyzate and the epoxy curing agent to form a high-hardness, high-light-transmittance hardened coating on the surface of the optically transparent nylon, and has a high Abbe number.
[0024] (2) In the present invention, a phenyl-containing silane coupling agent is further used for the silane hydrolyzate to further increase the refractive index of the hard coating. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0026] In order to obtain a transparent hardened coating compatible with optically transparent nylon, the hardened coating has good adhesion to the optically transparent nylon while improving the hardness of the optically transparent nylon, and can maintain a high Abbe number and refractive index of the optically transparent nylon, on the one hand, the present invention provides a hardening liquid composition, which comprises, by weight, 20-50 parts of multifunctional epoxy polyurethane, 40-80 parts of silane hydrolyzate and 0.3-2 parts of epoxy curing agent;
[0027] The number of epoxy groups in the multifunctional epoxy polyurethane is not less than 3, and the refractive index of the multifunctional epoxy polyurethane is not less than 1.53.
[0028] In the present invention, the functionality of the multifunctional epoxy polyurethane refers to the number of epoxy groups, and multifunctionality means that the number of epoxy groups is not less than 3, such as 3, 4, 5, 6, etc. In general, the more epoxy groups there are in the epoxy polyurethane, that is, the higher the functionality of the multifunctional epoxy polyurethane, the higher the hardness of the coating after cross-linking, but it may also cause the flexibility and adhesion of the coating to deteriorate.
[0029] The present invention adopts a multifunctional epoxy polyurethane with a relatively high refractive index in combination with a silane hydrolyzate, and after heat curing, a silicone-polyurethane composite hardening coating with high hardness, high refractive index and high Abbe number can be obtained on the surface of an optically transparent nylon. The use of an appropriate amount of multifunctional epoxy polyurethane can improve the crosslinking degree of the coating, which is beneficial to improving the hardness of the coating and also to improving the adhesion between the coating and the optically transparent nylon, which may be due to the fact that the polyurethane structure (-NHCOO-) can form more hydrogen bonds with the nylon (-NHCO-) structure at the interface, thereby improving the bonding force between the coating and the optically transparent nylon. In addition, the polyurethane structure has good flexibility, and can also have good flexibility when the hardness of the hardening coating is high.
[0030] In order to further improve the hardness of the hardened coating, the raw material components of the hardening liquid composition of the present invention may also include nano-scale inorganic non-metallic oxides, such as nano-SiO2 、Nano-TiO 2 、Nano ZrO 2 、Nano Al 2 O 3 , nano ZnO, etc. This is a commonly used technology in this field. The particle size of nano-scale inorganic non-metallic oxides is very low and will not affect the transmittance of light (especially visible light), so it will not affect the transmittance of the hardening coating. The weight proportion of nano-scale inorganic non-metallic oxides can be 1-20 parts. Nano-scale inorganic non-metallic oxides can also be prepared from commercially available sols, such as preparing nano SiO from silica sol. 2 . Furthermore, the surface of the nano-scale inorganic non-metallic oxide can be chemically bonded with an organic group, such as an epoxy group, an amine group, a methyl group, etc. The organic group can be chemically bonded with an organic group on the surface of the nano-scale inorganic non-metallic oxide through the reaction of a silane coupling agent, such as an amino-containing silane coupling agent, an epoxy-containing silane coupling agent, and exemplary silane coupling agents can be 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, β-aminoethyl-γ-aminopropyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, etc., or saturated silane coupling agents such as methyltrimethoxysilane and methyltriethoxysilane. Furthermore, for example, a combination of epoxy-containing silane coupling agent or amino-containing silane coupling agent and saturated silane coupling agent can be used, such as 3-aminopropyltrimethoxysilane and methyltrimethoxysilane in a molar ratio of 1:3-1:10. In this way, amine groups can be introduced on the surface of the nano-scale inorganic non-metallic oxide and participate in the cross-linking and curing reaction of the coating. At the same time, the amine content can be avoided to be too high, so as to avoid the cross-linking degree of the hardened coating being too high, which will lead to poor flexibility, adhesion, etc. of the coating.
[0031] In order to improve the workability of the hardening liquid composition, a solvent may be added to the hardening liquid composition to lower the viscosity, such as an alcohol solvent, such as anhydrous ethanol, isopropyl alcohol, etc.; an ether solvent, such as BCS, DPM, etc.; a ketone solvent, such as methyl ethyl ketone, cyclohexanone, etc.; an ester solvent, such as ethyl acetate, butyl acetate, etc. The amount of solvent used can be used as needed, such as 3-50 parts, or further, 5-30 parts.
[0032] In a preferred embodiment of the present invention, the raw material for preparing the multifunctional epoxy polyurethane is a combination of a polyol compound, xylylene diisocyanate and a hydroxy epoxy compound. By adopting the above technical scheme, the polyol compound can form a prepolymer with a terminal group of multiple isocyanate groups after reacting with xylylene diisocyanate, and then react with the hydroxy epoxy compound to obtain an epoxy polyurethane with a terminal group of multiple epoxy groups. The molecules of the above polyols contain no less than 3 hydroxyls, and the molecular weight is generally no more than 450. For example, glycerol, trimethylolpropane, pentaerythritol monoformate, pentaerythritol monoacetate, pentaerythritol monobutyrate, pentaerythritol monolaurate, pentaerythritol monostearate, pentaerythritol, etc.
[0033] In the present invention, the use of xylylene diisocyanate can make the obtained hardened coating have a higher refractive index and Abbe number. As an alternative, tetramethylxylylene diisocyanate can also be used instead of xylylene diisocyanate. It is a technology well known to those skilled in the art to prepare multifunctional epoxy polyurethane using a combination of preparation raw materials of polyol compounds, xylylene diisocyanate and hydroxy epoxy compounds. For example, a prepolymer with double-terminal isocyanate groups is first reacted with a polyol compound and xylylene diisocyanate, and then reacted with a hydroxy epoxy compound to obtain an epoxy polyurethane with multiple epoxy groups as the terminal group.
[0034] In a more preferred embodiment of the present invention, the molecular structure of the hydroxy epoxy compound contains 1 hydroxyl group and 1 epoxy group, the molecular weight does not exceed 300, and can be selected from one or a combination of two or more of glycidol, ethylene glycol monoglycidyl ether, diethylene glycol monoglycidyl ether, propylene glycol monoglycidyl ether and dipropylene glycol monoglycidyl ether.
[0035] The use of silane hydrolyzate to prepare a hard coating is a common technique for those skilled in the art. The performance of silane hydrolyzate prepared from different silane coupling agent raw materials is different, which will affect the performance of the hard coating. In a preferred embodiment of the present invention, the raw materials for preparing the silane hydrolyzate at least include phenylsilane coupling agent and amine-containing silane coupling agent. The use of phenylsilane coupling agent to prepare the silane hydrolyzate can increase the refractive index of the silane hydrolyzate, and then increase the refractive index of the hard coating, and is close to the refractive index of optically transparent nylon. Using an amine-containing silane coupling agent, an amino group can be introduced into the silane hydrolyzate, and participate in the curing reaction of the hard coating, thereby increasing the crosslinking density and hardness of the hard coating. In the present invention, the raw materials for preparing the silane hydrolyzate can also include alkyl orthosilicates, such as ethyl orthosilicate, methyl orthosilicate, etc., or can also include other types of silane coupling agents, such as saturated silane coupling agents, exemplified by methyltrimethoxysilane, n-butyltrimethoxysilane, etc.
[0036] In a more preferred embodiment of the present invention, the structure of the phenylsilane coupling agent is shown in the following formula (1):
[0037] R 1 (CH 2 ) a Me b Si(OR 2 ) 3-b (1)
[0038] Among them, R 1 is selected from phenyl or alkyl-substituted phenyl, R 2 Selected from C1-C4 alkyl, Me represents methyl, a=2-4, b=0-1.
[0039] The present invention adopts the phenyl silane coupling agent of the structure of the above formula (1), and there is an alkylene group between the phenyl group and the silicon atom, which can avoid the influence of the phenyl group on the hydrolysis and condensation of its alkoxysilyl group due to steric hindrance and the like, and the hydrolysis and condensation of the phenyl silane coupling agent is more sufficient, which is more conducive to obtaining a high light transmittance and stable hardening coating. For example, the phenyl silane coupling agent can be phenylethyltrimethoxysilane, phenylethyltriethoxysilane, 3-phenylpropyltrimethoxysilane, etc., which can be obtained by the corresponding phenyl olefin (such as styrene, allylbenzene) and hydrogen-containing silane coupling agent (such as trimethoxysilane) through a hydrosilylation reaction.
[0040] If the content of phenylsilane coupling agent in the raw material for preparing silane hydrolyzate is low, it is not conducive to improving the refractive index of the hard coating. If the content is too high, it may affect the hydrolysis and condensation of the silane hydrolyzate, and the hydrolysis and condensation are not complete. In a more preferred embodiment of the present invention, the weight proportion of phenylsilane coupling agent in the raw material for preparing silane hydrolyzate is not less than 20%. Furthermore, the weight proportion of phenylsilane coupling agent in the raw material for preparing silane hydrolyzate is not higher than 50%. For example, the weight proportion can be any value of 20%, 22%, 25%, 28%, 30%, 33%, 35%, 37%, 40%, 42%, 45%, 47%, 50%, etc. or any value in between, without special restrictions.
[0041] In a more preferred embodiment of the present invention, the structure of the amino-containing double-bond silane coupling agent is as shown in the following formula (2):
[0042] R 3 NHR 4 Me c Si(OR 5 ) 3-c (2)
[0043] Among them, R 3 is selected from H or C1-C4 alkyl, R 4 is absent, C1-C4 alkylene or substituted C3-C8 alkylene, R5 Selected from C1-C4 alkyl, Me represents methyl, c=0-1.
[0044] In the present invention, the amino-containing silane coupling agent can be 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, β-aminoethyl-γ-aminopropyltrimethoxysilane, β-aminoethyl-γ-aminopropyltriethoxysilane, etc., without particular limitation.
[0045] If the content of the amino-containing silane coupling agent in the raw material for preparing the silane hydrolyzate is low, the content of the amino groups introduced into the silane hydrolyzate is insufficient, and the cross-linking and cross-linking density and hardening effects are not obvious. If the amino group content is too high, the cross-linking density will be too high, which is not conducive to the flexibility and adhesion of the hardened coating. In a more preferred embodiment of the present invention, the weight proportion of the amino-containing silane coupling agent in the raw material for preparing the silane hydrolyzate is 3-10%. For example, the weight proportion can be any value of 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. or any value in between, without special restrictions.
[0046] On the other hand, the present invention also provides a hardened transparent optical nylon, which is composed of transparent optical nylon and a hardened layer arranged on the surface of the transparent optical nylon, and the hardened layer is prepared from the hardening liquid composition described in any of the above technical solutions. In the present invention, there is no particular limitation on the thickness of the hardened layer, and for example, it can be no more than 10 μm. The hardening liquid composition can be applied to the transparent optical nylon by spraying, spraying, dipping, pulling, etc.
[0047] In a preferred embodiment of the present invention, the hardening liquid composition is cured by heating to form a hardened layer. In the present invention, the epoxy curing agent used is not particularly limited, and can be a primary amino compound or a secondary amino compound, such as ethylenediamine, 1,4-butanediamine, 1,6-hexanediamine, polyetheramine, N,N'-dimethyl-1,8-octanediamine, N,N'-dimethyl-1,6-hexanediamine, N,N'-dimethyl-1,4-butanediamine, etc. There is no particular limitation on the heating temperature, but if it is too high, it may cause the transparent optical nylon to soften, so the recommended heating temperature can be 50-110°C, such as 50-70°C, 85-110°C, etc.
[0048] The technical solution of the present invention is further described and illustrated according to various embodiments below.
[0049] Example 1
[0050] Preparation of silane hydrolyzate:
[0051] The silane raw materials of the silane hydrolyzate are composed of phenylethyltrimethoxysilane, 3-aminopropyltrimethoxysilane, ethyl orthosilicate and methyltrimethoxysilane in a molar ratio of 30:5:30:35.
[0052] At room temperature, 1 kg of the above silane raw material was added to a reaction container, and 700 g of anhydrous ethanol and 500 g of deionized water were added. The mixture was stirred for reaction for 3 hours, and the temperature was raised to 60-70° C. and low boiling points were removed under reduced pressure to obtain a silane hydrolyzate.
[0053] Preparation of multifunctional epoxy polyurethane:
[0054] 1 mol of trimethylolpropane and 2 mol of xylylene diisocyanate were added to the reaction container, stirred at room temperature until the content of NCO groups remained unchanged, and then 1 mol of glycidol was added, stirred at room temperature for 1 hour, and heated to 50°C for 2 hours to obtain a multifunctional epoxy polyurethane. The refractive index of the multifunctional epoxy polyurethane was measured to be 1.55.
[0055] The raw material components of the curing liquid composition are composed of 300g of the above-mentioned multifunctional epoxy polyurethane, 600g of the above-mentioned silane hydrolyzate, 10g of N,N'-dimethyl-1,4-butanediamine, 100g of isopropyl alcohol and 100g of butyl acetate. The multifunctional epoxy polyurethane, silane hydrolyzate and butyl acetate are added to the reaction container, stirred and mixed evenly, and then N,N'-dimethyl-1,4-butanediamine is added, stirred and dissolved evenly, to obtain a curing liquid composition.
[0056] Example 2
[0057] The difference between this embodiment and embodiment 1 is that in embodiment 1, the amount of multifunctional epoxy polyurethane is adjusted from 300 g to 200 g, and the other steps remain unchanged.
[0058] Example 3
[0059] The difference between this embodiment and embodiment 1 is that in embodiment 1, the amount of multifunctional epoxy polyurethane is adjusted from 300 g to 500 g, and the other steps remain unchanged.
[0060] Example 4
[0061] The difference between this embodiment and embodiment 1 is that in embodiment 1, the silane hydrolyzate is adjusted from 600 g to 400 g. The other steps remain unchanged.
[0062] Example 5
[0063] The difference between this embodiment and embodiment 1 is that in embodiment 1, the silane hydrolyzate is adjusted from 600 g to 800 g. The other steps remain unchanged.
[0064] Example 6
[0065] The difference between this embodiment and embodiment 1 is that in embodiment 1, the raw material components of the hardening liquid composition further include 80g of modified SiO2 . The rest of the steps remain the same.
[0066] Modified SiO 2 The preparation method is as follows: 100g of untreated nano-SiO 2 Disperse in 1000g of anhydrous ethanol, add 3g of silane coupling agent (composed of 3-aminopropyltrimethoxysilane and methyltrimethoxysilane in a molar ratio of 1:6) and 3g of acetic acid, stir at room temperature for 3 hours, collect the solid, wash with anhydrous ethanol, and dry in an oven at 50°C overnight to obtain modified SiO 2 .
[0067] In the present invention, the untreated nano-SiO 2 It is prepared from silica sol. The specific preparation method is: add methanol, water and sodium dodecyl sulfate to alkaline silica sol, the weight of sodium dodecyl sulfate is 0.8% of alkaline silica sol, gradually add sulfuric acid solution under stirring to adjust the pH to 7.0, heat to 55°C and keep constant temperature for 2h, then heat to 400°C and dry for 6h, then grind and pass through a 2000 mesh sieve.
[0068] Example 7
[0069] The difference between this embodiment and embodiment 1 is that in embodiment 1, when preparing the silane hydrolyzate, phenylethyltrimethoxysilane is replaced by an equal mole of phenyltrimethoxysilane. The other steps remain unchanged.
[0070] Comparative Example 1
[0071] The difference between this comparative example and Example 1 is that in Example 1, when preparing the multifunctional epoxy polyurethane, xylylene diisocyanate is replaced by an equimolar amount of isophorone diisocyanate. The other steps remain unchanged.
[0072] The refractive index of the obtained multifunctional epoxy polyurethane was measured to be 1.44.
[0073] Comparative Example 2
[0074] The difference between this comparative example and Example 1 is that in Example 1, when preparing the multifunctional epoxy polyurethane, xylylene diisocyanate is replaced by an equimolar amount of hexamethylene diisocyanate. The other steps remain unchanged.
[0075] The refractive index of the obtained multifunctional epoxy polyurethane was measured to be 1.41.
[0076] Comparative Example 3
[0077] The difference between this comparative example and Example 1 is that in Example 1, when preparing the silane hydrolyzate, 3-aminopropyltrimethoxysilane is replaced by an equal molar amount of methyltrimethoxysilane. The other steps remain unchanged.
[0078] Comparative Example 4
[0079] The difference between this comparative example and Example 1 is that in Example 1, the multifunctional epoxy polyurethane in the raw material component of the hardening liquid composition is replaced by an equal weight of silane hydrolyzate. The other steps remain unchanged.
[0080] Example 8
[0081] Preparation of silane hydrolyzate:
[0082] The silane raw materials of the silane hydrolyzate are composed of phenylethyltrimethoxysilane, β-aminoethyl-γ-aminopropyltrimethoxysilane, ethyl orthosilicate and methyltrimethoxysilane in a molar ratio of 40:8:22:30.
[0083] At room temperature, 1 kg of the above silane raw material was added into a reaction container, and 800 g of anhydrous ethanol and 500 g of deionized water were added. The mixture was stirred for reaction for 3 hours, and the temperature was raised to 60-70° C. and low boiling points were removed under reduced pressure to obtain a silane hydrolyzate.
[0084] Preparation of multifunctional epoxy polyurethane:
[0085] 1 mol of pentaerythritol monoformate and 2.3 mol of xylene diisocyanate were added to the reaction container, stirred at room temperature until the content of NCO groups remained unchanged, 1.6 mol of ethylene glycol monoglycidyl ether was added, stirred at room temperature for 1 hour, 1 g of dibutyltin dilaurate was added, the temperature was raised to 50°C and reacted for 2 hours to obtain a multifunctional epoxy polyurethane. The refractive index of the multifunctional epoxy polyurethane was measured to be 1.58.
[0086] The raw material components of the curing liquid composition consisted of 400 g of the above-mentioned multifunctional epoxy polyurethane, 600 g of the above-mentioned silane hydrolyzate, 10 g of 1,6-hexanediamine, 80 g of isopropyl alcohol and 120 g of butyl acetate.
[0087] Example 9
[0088] The difference between this embodiment and embodiment 8 is that in embodiment 8, the silane raw material of the silane hydrolyzate is adjusted to consist of phenylethyltrimethoxysilane, β-aminoethyl-γ-aminopropyltrimethoxysilane, ethyl orthosilicate and methyltrimethoxysilane in a molar ratio of 40:3:22:35. The other steps remain unchanged.
[0089] Example 10
[0090] The difference between this embodiment and embodiment 8 is that in embodiment 8, the silane raw material of the silane hydrolyzate is adjusted to consist of phenylethyltrimethoxysilane, β-aminoethyl-γ-aminopropyltrimethoxysilane, ethyl orthosilicate and methyltrimethoxysilane in a molar ratio of 40:12:22:26. The other steps remain unchanged.
[0091] Performance Testing
[0092] The hardening liquid compositions of Examples 1-10 and Comparative Examples 1-4 were sprayed onto the surface of optically transparent nylon, and baked at 85° C. for 2 hours to obtain hardened nylon.
[0093] Light transmittance: According to the method of GB / T2410-2008, the light transmittance in the visible light region was tested using a UV-visible spectrophotometer.
[0094] Refractive index: tested using a digital Abbe refractometer.
[0095] Abbe number: tested using a multi-wavelength Abbe refractometer.
[0096] Adhesion: Tested according to the method of GB / T9286-1998.
[0097] Impact strength: Tested in accordance with the method of GB / T22374-2018.6.3.10, the highest impact energy at which no cracks appear in the test coating.
[0098] Hardness: Tested in accordance with GB / T 6739-2006.
[0099] The results are shown in Table 1 below.
[0100] Table 1
[0101]
[0102]
[0103] The data in Table 1 above show that the hardening liquid composition of the present invention is suitable for optically transparent nylon, and still has a relatively high refractive index and Abbe number after the surface of the optically transparent nylon is hardened.
[0104] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.
Claims
1. A hardening liquid composition, characterized in that: The raw material components include, by weight: 20-50 parts of multifunctional epoxy polyurethane, 40-80 parts of silane hydrolyzate and 0.3-2 parts of epoxy curing agent; The number of epoxy groups in the multifunctional epoxy polyurethane is not less than 3, and the refractive index of the multifunctional epoxy polyurethane is not less than 1.
53.
2. The hardening liquid composition according to claim 1, characterized in that The raw materials for preparing the multifunctional epoxy polyurethane are a combination of a polyol compound, xylylene diisocyanate and a hydroxy epoxy compound.
3. The curing liquid composition according to claim 2, characterized in that The hydroxy epoxy compound is selected from one or a combination of two or more of glycidyl alcohol, ethylene glycol monoglycidyl ether, diethylene glycol monoglycidyl ether, propylene glycol monoglycidyl ether and dipropylene glycol monoglycidyl ether.
4. The hardening liquid composition according to claim 1, characterized in that The raw materials for preparing the silane hydrolyzate at least contain a phenyl silane coupling agent and an amino-containing silane coupling agent.
5. The curing liquid composition according to claim 4, characterized in that: The structure of the phenylsilane coupling agent is shown in the following formula (1): R 1 (CH2) a Me b Si(OR 2 ) 3-b (1) Among them, R 1 is selected from phenyl or alkyl-substituted phenyl, R 2 Selected from C1-C4 alkyl, Me represents methyl, a=2-4, b=0-1.
6. The curing liquid composition according to claim 4, characterized in that The weight proportion of the phenylsilane coupling agent in the raw materials for preparing the silane hydrolyzate is not less than 20%.
7. The curing liquid composition according to claim 4, characterized in that: The structure of the amino-containing silane coupling agent is shown in the following formula (2): R 3 NHR 4 Along with c Si(OR 5 ) 3-c (2) Among them, R 3 is selected from H or C1-C4 alkyl, R 4 is absent, C1-C4 alkylene or substituted C3-C8 alkylene, R 5 Selected from C1-C4 alkyl, Me represents methyl, c=0-1.
8. The curing liquid composition according to claim 4, characterized in that: The aminosilane coupling agent accounts for 3-10% by weight of the raw materials for preparing the silane hydrolyzate.
9. A hardened transparent optical nylon, characterized in that: The invention comprises transparent optical nylon and a hardening layer arranged on the surface of the transparent optical nylon, wherein the hardening layer is prepared from the hardening liquid composition according to any one of claims 1 to 8.
10. The hardened transparent optical nylon according to claim 9, characterized in that: The curing liquid composition is cured by heating to form the hardened layer.
Citation Information
Patent Citations
Room temperature curing organic silicon transparent hard coating material and preparation method thereof
CN112876987A
Coating composition and preparation method thereof
CN116218353A
Transparent resin substrate
US20140248478A1